But is it science?. Issue 2 (1st February 2017) - Watts, Mike; Salehjee, Saima; Essex, Jane
ABSTRACT: Early years science education is not science, but a curricular construction designed to induct young children into a range of ideas and practices related to the natural world. While inquiry-based learning is an important approach to this, it is not of itself unique to science and there are a range of logico-mathematical constructions that come closer to the essence of science. In this paper we discuss just three: empirical question-asking, transgressive play, and good thinking. The challenge, of course is to induct early years practitioners to a different way of shaping early science.